Synthesis and application of activated biochar from the slow pyrolysis of municipal solid wastes for the removal of organic contaminants from aqueous solutions - Genuino, Divine Angela D.
With the growing issues on municipal solid waste (MSW) management and disposal and the accompanying environmental concerns, the pyrolysis of MSW to produce high value products is becoming a promising technology to reduce MSW in landfills without harmful environmental repercussions. In this work, the slow pyrolysis of the usual MSW residuals, such as paper, yard wastes and textiles, is investigated. The influence of operating temperature (350-550 degree celsius) on the biochar, gas and pyrolytic liquid products is evaluated. The highest yields of the biochar (45.2 percent), pyrolytic liquid (37.1 percent) and gas product (25.7 percent) were obtained at 350, 450 and 500 degree celsius, respectively. The amount of combustible gases, i.e. Hz and CH4, also increased with temperature. In addition, the effect of the co-pyrolysis of MSW with coconut husk (CH) is also explored. Co-pyrolysis experiments showed enhanced biochar and combustible gases production. Moreover, more phenols were detected in the pyrolytic liquid obtained from co-pyrolysis. The biochar products were utilized as adsorbent material for the removal of organic contaminants. Adsorption of methylene blue (MB) dye showed that the co-pyrolysis biochar was able to remove 80.5% more MB solute than the MSW pyrolysis biochar. Isotherm studies of the co-pyrolysis biochar showed that the Langmuir model best described the system, with maximum capacities ranging between 27.6 and 32.7 mg g'. Thermodynamic analysis showed that MB adsorption onto the co-pyrolysis biochar is spontaneous (4G-=-1.2 to -4.5 kJ mol-1) and endothermic (AH=46.5 kJ mol-'). Chemical and thermal modifications were also done on the MSW pyrolysis biochar to improve its specific surface area. Optimization of the activation parameters, i.e. KOH concentration, activation temperature and time, using central composite design (CCD) enhanced the biochar surface area from 402.8 to 662.4 m2 g". Furthermore, surface modifications also led to the improvement of the MB adsorption with the Langmuir maximum adsorption capacity of 37.0-41.2 mg g'. Acetaminophen (APAP) adsorption onto the activated biochar was also explored which achieved a Langmuir maximum capacity of 14.7-18.3 mg g'. The adsorption rate was generally controlled by diffusion mechanisms and chemical surface reactions. Thermodynamic analysis showed the adsorption systems were spontaneous and endothermic. Finally, the potential extraction of humic substances from MSW biochar during the chemical activation process using KOH was explored to enhance the value of spent reagents and add further applications of the pyrolysis products. Artificial neural network was employed to model and optimize the humic acid (HA) extraction from biochar by varying KOH concentration, extractant dose, contact time and precipitant volume. The optimum HA yield of 187.5 mg g' was obtained at [KOH] 0.50 M, extractant dose = 30 g L", time = 12 h, and precipitant volume = 1.82 mL. The KOH concentration had the greatest effect on the HA yield followed by precipitant volume.